3D composite electrodes of microbial fuel cells used in livestock wastewater: Evaluations of coating and performance. (9th November 2017) - Lai, Mei-Feng; Lou, Ching-Wen; Lin, Jia-Horng
Abstract: This study investigates the influence of using zinc- (FZ) and nickel-coated (FN) 3D anode electrodes on the electricity yield of the two-chambered cubic microbial fuel cells (MFCs) in terms of the electricity production efficacy. Swine wastewater is used as seed inoculums matrix that serves as feedstock in the anode chamber. The FN-electrodes exhibit a high corrosion and anti-oxidation resistance in a 28-day oxidation process based on the EDX observation. In addition, a 3D electrode structure efficiently provides a large surface area that benefits electron transfer. FN-C3 electrodes have a voltage of 638.9 mV, a power density of 138.6 mW/m 2, and chemical oxygen demand (COD) removal rate of 72.1%. Highlights: Using a 3D-coated Ni electrode as the anode creates a high weathering tolerance. Ni electrode is featured with good electrical conductivity, high corrosion resistance. The COD removal efficiency of the coated Ni electrodes reaches above 72%.